Design Optimization of Crashworthiness in Square Tube as Thin Walled Structure With Variations of Crush Initiator: Stripe-Parallelogram-Trigon - Felix Dionisius; Jos Istiyanto; Tito Endramawan; Andri Andri (P3M Politeknik Negeri Indramayu, 2018)
Crashworthiness is an ability of a vehicle structure in order to reduce injury when occurred in collision. Crashworthiness criteria are peak force (Fmax), specific energy absorption (SEA), and crush force efficiency (CFE). The part of structure of vehicle in crashworthiness is front rail which is generally tube as thin walled structure. The aim was to know the best design in thin walled square tube as specimen by variance of crush initiator which arranged holes 3 mm of diameter in shaping stripe with 4 holes, then added graded holes in parallelogram to trigon. This research used compression experiment method under quasi static loading with 30 mm/minute of actuator velocity. Optimum design was done by using Multi Criteria Decision Making (MCDM) with Simple Additive Weighting (SAW) modelling. This research presents that specimen with trigon of crush initiator is the best design with 0.98 of decision score in which crashworthiness criteria for peak force, specific energy absorption and crush force efficiency are 19193.81 N; 5100.93 J/kg; and 46.44%.